Theoretical Approaches to the Definition of “Critical Space Infrastructure” - Maksym Sokiran (Advanced Space Law, 2020)
The article analyzes various scientific approaches to the definition of such interdependent concepts as “critical space infrastructure” and “critical information infrastructure.” To clarify these concepts, the legislative initiatives of different countries are compared. It is concluded that despite the lack of a legitimate definition of “critical space infrastructure,” it is a complex system consisting of physical and virtual information resources that need to be controlled and secured because if it is vulnerable (not resistant to risks), it can lead to a crisis many vital systems of any state in general or in a particular industry — in particular. Therefore, it needs new approaches to protect it from attacks.